Use of preneoplastic lesions in colon and liver in experimental oncology - Ehrlich, Veronika A. (Radiology and oncology (Ljubljana), 2004)
The present article gives a brief overview on the use of altered hepatic foci (AHF) and aberrant crypt foci (ACF) in the colon in experimental cancer research. These foci are easily detectable preneoplastic lesions, which have been discovered approximately 30 years ago. AHF and ACF are valuable tools forthe detection of cancer- initiating and promoting compounds, and for the detection of chemoprotective agents. They were also successfully used in numerous studies aimed at elucidating the molecular mechanisms of early neoplasia, such as alterations of the expressions of oncogene and tumor suppressor genes, and changes in the activities of cancer associated enzymes.
Keywords: Barbiturates; Barbiturati; Bolezen, živalski modeli; Carcinogens; Chemically Induced; Colonic Neoplasms; debelo črevo; Debelo črevo, novotvorbe; Disease Models, Animal; Genetics; jetra; Jetra, novotvorbe eksperimentalne; Karcinogeni; Liver Neoplasms, Experimental; Mutacija; Mutation; Nitrosamines; Nitrozamini; novotvorbe; onkologija; Physiopathology; Precancerous Conditions; Prekanceroze; tumor